Flowering time in banana (Musa spp.), a day neutral plant, is controlled by at least three FLOWERING LOCUS T homologues - Akhilesh K. Chaurasia (Nature Portfolio, 2017)
Abstract Banana is an important day neutral food crop with a long flowering/fruiting cycle that is affected by hot summers or cold winters in different places. Manipulating its life cycle requires an understanding of its flowering time machinery to bypass these stresses. Twelve FLOWERING LOCUS T (FT) and two TWIN SISTER OF FT (TSF) members were isolated from banana and their organization and expression pattern studied during development in two varieties that differ in flowering time namely Grand Nain (AAA genotype) and Hill banana (AAB genotype). The expression of at least 3 genes namely MaFT1, MaFT2 and MaFT5 (and to some extent MaFT7) increases just prior to initiation of flowering. These four genes and five others (MaFT3, MaFT4, MaFT8, MaFT12 and MaTSF1 could suppress the delayed flowering defect in the Arabidopsis ft-10 mutant and induce early flowering upon over-expression in the Col-0 ecotype. Most genes are diurnally regulated and differentially expressed during development and in various vegetative and reproductive tissues suggesting roles besides flowering. Subtle amino acid changes in these FT/TSF-like proteins provide interesting insights into the structure/function relationships of banana FTs vis-à-vis Arabidopsis. The studies provide a means for manipulation of flowering in banana for better management of resources and to reduce losses through abiotic stresses.